2018
DOI: 10.1111/ans.14555
|View full text |Cite
|
Sign up to set email alerts
|

Mobility scores as a predictor of length of stay in general surgery: a prospective cohort study

Abstract: The DEMMI score is a fast, easy and useful tool to, on post-operative day 1, predict discharge within 1 week. The utility of this is to act as an anticipatory trigger for more proactive and efficient discharge planning in the early post-operative period, and there is potential to use the DEMMI as a comparator in clinical trials to assess functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to explore the relationship between DEMMI scoring and sarcopenia. While previous research has indicated that the DEMMI score is a useful tool for determining patient outcomes, 12–14 we did not see an association with sarcopenia. This may possibly be due to the skewed DEMMI scores (median DEMMI = 100) seen in our study, reflecting a high level of pre‐operative mobility.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study to explore the relationship between DEMMI scoring and sarcopenia. While previous research has indicated that the DEMMI score is a useful tool for determining patient outcomes, 12–14 we did not see an association with sarcopenia. This may possibly be due to the skewed DEMMI scores (median DEMMI = 100) seen in our study, reflecting a high level of pre‐operative mobility.…”
Section: Discussioncontrasting
confidence: 97%
“…11 After general surgical procedures, a worse pre-operative DEMMI score is associated with longer inpatient admission. 12 It has been increasingly used for predicting functional recovery after surgery. 13,14 Despite a close relationship between mobility scores and sarcopenia, the association between DEMMI score and sarcopenia has not been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study where DEMMI is performed in surgical patients (20–87 years), documents that the DEMMI score can predict discharge within 1 week [30]. The present study confirms these results in an acute geriatric population, although the predictive accuracy that we show is slightly lower.…”
Section: Discussionsupporting
confidence: 84%
“…The DEMMI has been validated for use in mobility assessment as an initial tool and for generating intrapatient interval change comparative data . It has also been validated in the surgical setting by objectively determining readiness for discharge and LOS for patients following colectomy . As a result, it has been used in previous research to compare functional outcomes following colectomy and appeared to be a sensitive discriminator of recovery in this trial .…”
Section: Discussionmentioning
confidence: 99%